Software radio architecture a mathematical perspective. - Mitola, J., III
As the software radio makes its transition from research to practice, it becomes increasingly important to establish provable properties of the software radio architecture on which product developers and service providers can base technology insertion decisions. Establishing provable properties requires a mathematical perspective on the software radio architecture. This paper contributes to that perspective by critically reviewing the fundamental concept of the software radio, using mathematical models to characterize this rapidly emerging technology in the context of similar technologies like programmable digital radios. The software radio delivers dynamically defined services through programmable processing capacity that has the mathematical structure of the Turing machine. The bounded recursive functions, a subset of the total recursive functions, are shown to be the largest class of Turing-computable functions for which software radios exhibit provable stability in plug-and-play scenarios. Understanding the topological properties of the software radio architecture promotes plug-and-play applications and cost-effective reuse. Analysis of these topological properties yields a layered distributed virtual machine reference model and a set of architecture design principles for the software radio. These criteria may be useful in defining interfaces among hardware, middleware, and higher level software components that are needed for cost-effective software reuse
Keywords: Turing machine; Turing-computable functions; Bounded recursive functions; Cost-effective software reuse; Hardware; Interfaces; Layered distributed virtual machine reference model; Mathematical models; Middleware; Plug-and-play applications; Product developers; Programmable digital radios; Programmable processing; Provable properties; Service providers; Software components; Software radio architecture; Stability; Topological properties; Total recursive functions